(untitled) (El-Wahat Journal for Research and Studies, 2025)
This study aims to provide a analytical vision of the role of parents and educators in achieving a digital security culture for Algerian child, in light of the “National guide for child online protection” issued in 2020, which includes many instructions for such educators that to protect the child from the risk of using internet. Since it is impossible to prevent them from using it. Using the descriptive analytical method, this study a set of conclusions, which are: -The guide provided several guidelines focusing on the need for parents to provide the child with the basics of culture digital security control based on the adoption of censorship and self-inflicted behavior and to talk them about the dangers of the digital world. - However, the guide was not been circulated sufficiently to benefit from which must be remedied, and needs to be updated in accordance with developments in the digital environment. Key words: - Digital security, child, parents, role, Internet risk.